Analysis of the Implementation of Corporate Social Responsibility (CSR) in Islamic Financial Institutions in the Triple Bottom Line Perspective (Study at PT BPRS Puduarta Insani) - Rafika Hayati Dalimunthe; Muhammad Arif; Laylan Syafina (The ES Accounting And Finance, 2022)
This study aims to analyze the implementation of Corporate Social Responsibility (CSR) at PT BPRS Puduarta Insani and see its suitability with the triple bottom line concept. The research method used in this study is a descriptive qualitative approach. The types of data used are primary and secondary data. Primary data were obtained through interviews with the President Director and Personnel Staff of PTBPRS Puduarta Insani. Secondary data were obtained from books, scientific journals, theses and other documents related to research. Data collection techniques used observation, interviews and documentation. The data analysis is done by reducing the data, presenting the data, verifying the data and drawing conclusions. Based on the results of research conducted at PT BPRS Puduarta Insani, it can be concluded that the implementation of CSR has been going well. When viewed from the triple bottom line concept, CSR at PT BPRS Puduarta Insani has been carried out well in the aspects of profit and people. Economic responsibility (profit) can be seen from the company's commitment to remain focused on profits for the survival of the company and set aside 4% to 5% of annual profit for CSR activities. Social responsibility (people) is actually implemented through CSR programs such as donations for orphans, scholarships, mosque construction and other social activities. It's just that on the planetary aspect, PT BPRS Puduarta Insani has never carried out activities that are in direct contact with nature, only within the company's internal scope, such as when Covid-19 provided a place for washing hands and hand sanitizers, while maintaining the cleanliness and comfort of the work environment so that employees those who work feel comfortable.